Application of the DNA Molecular Markers RM20A and RM241 on King Grass (Pennisetum purpuphoides) and Dwarf Elephant Grass (Pennisetum pupureum cv. Mott) - Islami, Romi Zamhir; Ari Zindhi, Muhammad Amrullah; Mansyur; Susilawati, Iin (Jurnal Ilmu-Ilmu Peternakan, 2024)
Feed, as the main element that provides livestock nutrition, is composed of two components, namely, concentrate and forage. Examples of commonly used forages are king grass and dwarf elephant grass. These grasses are very familiar among farmers because they have good crude protein (CP) content; specifically, the CP content of king grass is 13,50% (Siswanto et al., 2016), and the CP content of dwarf elephant grass is 14,35% (Erleli, 2020). Forage production can be disrupted by weather factors. In the dry season, the production of king grass and dwarf elephant grass decreases by 50%. As a result, there is a forage crisis in the dry season. To overcome this, genetic improvement of king grass and dwarf elephant grass is possible. Previous research has succeeded in finding primers RM20A and RM241, each of which can lead to new traits in rice plants, namely, leaf rolling and plant height. This primer can be applied to king grass and dwarf elephant grass to increase the production potential of these plants and increase plant resistance in the dry season. This research uses the PCR technique to amplify primers from the template DNA of king grass and dwarf elephant grass. Optimization was carried out via several procedures due to species differences among rice, king grass and dwarf elephant grass. The results revealed that the RM241 primer could not be amplified at all in king grass plants and was amplified only in dwarf elephant grass. Moreover, the RM20A primer produced better results, where amplification could occur in both plants. This may be due to several factors, such as the condition of the DNA template, the condition of the materials and the possibility of human error. Amplification of the two primers also revealed that they were polymorphic, indicating that these two primers could not accurately amplify SSRs in king grass and dwarf elephant grass. This also causes many smears in the visualization of the PCR results. Overall, this research was able to determine the plant height and leaf rolling characteristics of king grass and dwarf elephant grass.